UPAYA PEMERINTAH INDONESIA DALAM MELINDUNGI WARGA NEGARA INDONESIA DI LUAR NEGERI (STUDI KASUS: PEROMPAKAN KAPAL FV NAHAM 3) - Utari Angdriani; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
protecting its citizens who are overseas with a case study of piracy of the FV Naham 3. The FV Naham 3 is an Oman-flagged ship and is a victim of piracy by Somali pirates in the south of the Seychelles . The ship is known to carry 29 crews (ABK) from several countries in Asia such as China, Philippines, Vietnam, Taiwan, Cambodia and Indonesia. This research uses the perspective of Neorealism, Diplomacy theory, and the concept of Human Security. The diplomacy model that the author uses is multitrack diplomacy by Joseph Montville. There are 2 tracks diplomacy from multitrack diplomacy by Joseph Montville, namely track one is diplomacy carried out by state actors, while track two is diplomacy carried out by negotiators who are not representatives of a government.The rescue process carried out by the Indonesian government and respective governments whose citizens were also victims of the Somali pirates being held hostage throughout 2012-2014, had yet to get results. After the efforts that had not been made, the state governments whose citizens had been taken hostage built communication and provided information to one another regarding the condition of the victims and the Somali pirates so that the release could be carried out immediately. After establishing communication with the governments of other countries, the Indonesian government through the Ministry of Foreign Affairs and BIN appointed Holman Fenwick Willan who then collaborated with Oceans Beyond Piracy (OBP) and formed a rescue team for victims of the Somali pirate hostage under the name Hostage Support Partnership (HSP). Countries whose citizens were also victims of hostage taking also provided various financials and material assistance in this process of release. Until finally, on October 22, 2016 the HSP team led by John Steed managed to save the hostages.Keywords: Hostages, Multitrack Diplomacy, Somali Pirates, FV Naham 3.